Makna Tauhid dalam Perspektif Tasawuf dan Urgensinya Bagi Kehidupan Sosial Masyarakat - Rahayu, Endang Sri (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2019)
Human life in modern times, with various their advances, often overrides the spiritual. As a result, in addition to being dry from inner intake, their lives rely solely on the fulfillment of worldly satisfaction. More than that, denying the spiritual side also makes a person's religious understanding seem rigid and exclusive, so it is not uncommon for religious notions to be born that actually cause public unrest. His life activities are not based on his personal basis as a servant. In the study of Sufism, discussed the meaning of monotheism in depth, which has spiritual values ​​that are relevant to human life in modern times. Monotheism as the most basic principle of life is upheld. There are several typologies of monotheism in Sufism, including monotheism dzati, monotheism sifati, monotheism af'ali, monotheism syuhudi, and monotheism wujudi. Each has unique characteristics and meanings that differ from one another. Although in essence, all forms of monotheism must be achieved with practical efforts both by purifying the soul or by other means that can lead to an essential understanding of the nature of Allah SWT. That way, it can be a balancer of modern-day human life.